BIM-based scheduling for precast assembly and tower crane lifting - Huang, Lihui (Nanyang Technological University, 2021)
With the increasing popularity of Building Information Modelling (BIM) in the building and construction industry worldwide and the development of the precast industry, three issues have become significant. The first one is the path planning of the tower crane lifting of heavy precast. It is crucial to determine how to lift the precast that becomes larger and heavier. Lifting not being properly planned can cause safety issues even accidents. Good lift planning, on the other hand, can improve productivity. The second issue is the precast installation/assembly sequence. Improper installation sequence may lead to undo and redo undesired work for lifting and assembling of precast components. The third one is related to the dynamic nature of the real construction environment. It is necessary to capture the changing real environment in the lifting and assembly processes.